2023
DOI: 10.3390/ijerph20064955
|View full text |Cite
|
Sign up to set email alerts
|

Potentially Inappropriate Medication at Admission and at Discharge: A Geriatric Study in an Internal Medicine Service in Portugal

Abstract: Aging is associated with an increase in the prevalence of chronic diseases and polypharmacy, and with the prescription of potentially inappropriate medications (PIMs). This study aimed to analyze the variation in PIMs from hospital admission to discharge. A retrospective cohort study was conducted on inpatients of an internal medicine service. According to the Beers criteria, 80.7% of the patients had been prescribed at least one PIM at admission and 87.2% at discharge; metoclopramide was the most-prescribed P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…In this direction, several studies have reported that the inadequate prescription of BZD, according to STOPP criteria, are found among the most frequent PIM [ 31 , 32 , 38 ]. However, other studies did not find use of BZD as any of the most detected PIM [ 26 ], probably due to the struggles in determining prescription adequacy retrospectively. Interestingly, through our clinical committee review process, we have been able to reduce the prescription of BZD between 63 and 75%, depending on the criteria, in the internal medicine and the geriatric services.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In this direction, several studies have reported that the inadequate prescription of BZD, according to STOPP criteria, are found among the most frequent PIM [ 31 , 32 , 38 ]. However, other studies did not find use of BZD as any of the most detected PIM [ 26 ], probably due to the struggles in determining prescription adequacy retrospectively. Interestingly, through our clinical committee review process, we have been able to reduce the prescription of BZD between 63 and 75%, depending on the criteria, in the internal medicine and the geriatric services.…”
Section: Discussionmentioning
confidence: 96%
“…The optimization of medical prescription in older patients, with the final goal of diminishing PIDP incidence, is one of the main concerns among clinical teams. In fact, several studies retrospectively comparing the incidence of PIDP between patients’ admission and discharge have been reported in the last years [ 26 30 ]. Nevertheless, they were performed in a retrospective manner and provide contradictory results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding nursing home residents, PIM was observed in 86.4% [ 30 ]. Recently, one study also found that the number of PIMs at discharge was higher than at admission in Portuguese geriatric inpatients of an internal medicine service [ 31 ].…”
Section: Introductionmentioning
confidence: 99%